2008
DOI: 10.4269/ajtmh.2008.79.911
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Lethality in Severe Leptospirosis in Urban Brazil

Abstract: To ascertain prognostic factors associated with fatal outcomes in severe leptospirosis, a retrospective case-control study was done using population-based surveillance data. Centralized death certificate reporting of leptospirosis mortality was combined with details of patients' hospitalizations, which were obtained from hospitals representing all sectors of São Paulo city. Among identified leptospirosis cases, 89 lethal cases and 281 survivor cases were analyzed. Predictors of death included age>40 years, dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
6
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(146 citation statements)
references
References 15 publications
13
111
6
16
Order By: Relevance
“…This is contrary to findings by Dupont et al 18 and Spichler et al 15 It is important to note that the renal parameters serum creatinine > 2 and blood urea were not associated with mortality. However, oliguria and anuria were associated with mortality outcomes.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This is contrary to findings by Dupont et al 18 and Spichler et al 15 It is important to note that the renal parameters serum creatinine > 2 and blood urea were not associated with mortality. However, oliguria and anuria were associated with mortality outcomes.…”
Section: Discussioncontrasting
confidence: 56%
“…Advanced age was found to be associated with mortality by Chawla et al 9 and Spichler et al 15 Chawla et al in the same study also found chronic alcoholism 9 to be associated with the same. Although male sex has been found to be associated with mortality by Chawla et al 9 , other studies have challenged such assumption.…”
Section: Factors Associated With Mortalitysupporting
confidence: 49%
See 1 more Smart Citation
“…In most urban environments endemic for leptospirosis, including São Paulo City, the major sources of infection are urban rodents and sometimes dogs. [3][4][5] One potential source of leptospiral infection is bats. Bats are known to carry some human pathogens, including Leptospira , [6][7][8][9] as well as rabies 10 and histoplasmosis.…”
Section: Introductionmentioning
confidence: 99%
“…Poor urban settings present potentially ideal ecological conditions for the transmission of leptospirosis. 3,4 The source of leptospiral infection to humans is typically direct or indirect contact with the urine of infected animals. In most urban environments endemic for leptospirosis, including São Paulo City, the major sources of infection are urban rodents and sometimes dogs.…”
Section: Introductionmentioning
confidence: 99%